Chlorophyll print: transformation of man made conventional technology photographic process into natural process (photosynthesis) / Dona Lowii Madon … [et al.] - Madon, Dona Lowii; Nik Aziz, Nik Nor Azidah; Wan Mohd Zain, Wan Nor Ayuni; Baharuddin, Nor Fariza; Abd Samat, Raziq (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2012)
The glorious past hidden each facade, Malacca has became the city that boasts a two-pronged development via industrialization and tourism. As an environmentally photograph produced via chlorophyll prints, we considered this raise awareness idea is on finding an alternative process for non-chemical uses in photography. A review of the literature through Binh Danh Chlorophyll Process reveals that by placing a negative in contact with living leaf and then exposing it to sunlight, the image literally becomes part of the leaf. This process deals with the idea of elemental transmigration - from conventional method of photography developing process to natural process (photosynthesis). The faded colours of the leaves and detail of the lines and veins indirectly represent the time element that creates historical contacts whereby Malacca heritage items are used in this research. This research therefore explores the potentiality of local weather of Malaysia to achieve this experiment. The result of the experiment is an art piece in a form of postcard with Malacca identities as the limitation.